Indeks Kepuasan Masyarakat (Ikm) Pada Badan Penanggulangan Bencana Daerah Kabupaten Kutai Kartanegara Tahun 2019 - Ali Akbar (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract: The Regional Disaster Management Agency has the main task of assisting the Regent in carrying out Government Affairs which is the authority of the Region and the Assistance Task for Regional Disaster Management. This task is very responsible for disaster management that occurred in Kutai Kartanegara Regency. Regarding this, evaluation of the implementation of duties and functions needs to be carried out regularly and continuously to maintain and improve the quality of services to the community. This study aims to determine community satisfaction with the Service Performance of the Regional Disaster Management Agency of Kutai Kartanegara Regency and to determine the suitability of service conditions as expected by the community. This study uses 5 (five) dimensions of service quality, these dimensions are Tangibles, Reliability Responsiveness, Assurance, Empathy as variables measuring community satisfaction. The research results show that out of 9 (nine) sub-district work areas, only 3 sub-districts were declared good in this survey. Based on the order (ranking) of performance levels based on the order of the average score, Kota Bangun District was in the highest rank with Good service performance, then Anggana District then Sebulu District, while 6 other Districts were declared Poor in order, namely Samboja, Tenggarong Seberang, Muara Jawa. , Sanga-Sanga, Marang Kayu and Loa Janan. Keywords : Service quality, Customer satisfaction, Disaster.